International Conference on Computer Application and Information Security (ICCAIS 2021) 2022
DOI: 10.1117/12.2637385
|View full text |Cite
|
Sign up to set email alerts
|

Research of garbage salvage system based on deep learning

Abstract: The increase in surface trash salvage tasks has led to problems such as high staff workload, high labor costs, and low work efficiency. A garbage salvage system with autonomous cruising, identification, and detection is designed for this problem. This paper is based on deep learning technology to detect surface garbage and salvage garbage by robotic arm to solve the problem of low intelligence of surface garbage salvage as well as the problem caused by rising labor cost and insufficient labor, and to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…TF40 is an millimeter-level accuracy LiDAR with a range of up to 40 m [ 36 , 37 , 38 ]. Accuracy in mm is essential because the trash object is relatively small, 15 cm × 20 cm.…”
Section: Methodsmentioning
confidence: 99%
“…TF40 is an millimeter-level accuracy LiDAR with a range of up to 40 m [ 36 , 37 , 38 ]. Accuracy in mm is essential because the trash object is relatively small, 15 cm × 20 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental results showed that YOLOv3 achieved higher detection accuracy compared to the other four algorithms. Yang et al [17] designed a garbage collection system with autonomous cruising, recognition, and detection capabilities, equipped with the ROS robot operating system and utilizing the YOLO v4 object detection model to detect garbage, which was then applied to an intelligent garbage collection system using the detected targets and their location information. Kong et al [18] proposed an intelligent robot system, IWSCR, for water surface cleaning, where the core component of the visual system was designed based on YOLOv3.…”
Section: Water Surface Garbage Detectionmentioning
confidence: 99%